2017
DOI: 10.7860/jcdr/2017/26062.10227
|View full text |Cite
|
Sign up to set email alerts
|

Candida Albicans Infection Masquerading as a Soft Tissue Tumour Diagnosed by Fine Needle Aspiration Cytology

Abstract: A 60-year-old male, diabetic presented with a soft tissue mass over the right forearm of 15 days duration. The swelling was 5 x 3 cm and a clinical diagnosis of neurofibroma was made. Fine Needle Aspiration Cytology (FNAC) was done using standard technique. Smears showed predominantly suppurative inflammation, foreign body giant cells, granulomas and fungal hyphae. KOH mount, culture and germ tube test was positive. Final diagnosis of fungal granuloma was made. Fungal infections should be included in the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…[Color figure can be viewed at wileyonlinelibrary.com] immunocompromised patients. 5 The incidence of Candida infection has increased in the recent 20 years possibly due to immunosuppression, travel, and environmental exposure. 6 It is generally underappreciated that while Candida is an opportunistic pathogen, the majority of patients (approx.…”
Section: Discussionmentioning
confidence: 99%
“…[Color figure can be viewed at wileyonlinelibrary.com] immunocompromised patients. 5 The incidence of Candida infection has increased in the recent 20 years possibly due to immunosuppression, travel, and environmental exposure. 6 It is generally underappreciated that while Candida is an opportunistic pathogen, the majority of patients (approx.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of Aspergillus depends on host immunity and can have varied presentations ranging from violaceous macules, to papules, hemorrhagic bullae, pustules, and subcutaneous abscess to ulcerative lesions. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…It can occur either by hematogenous route or traumatic inoculation. [ 5 ] Jinkala et al . in their 9-year study from South India have identified fungal elements on cytology in 24 out of 29 cases, of them 16 were reported as phaeohyphomycosis and four cases were reported as Aspergillus .…”
Section: Discussionmentioning
confidence: 99%
“…3,5 The possibility of Candida infection should be considered in such unimproved infections. 15 Early recognition with prompt treatment is mandatory to prevent sequelae of candidiasis and its haematogenous or contiguous spread. 15 Early recognition with prompt treatment is mandatory to prevent sequelae of candidiasis and its haematogenous or contiguous spread.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Clinicians should also remember how simple traditional routine clinical tests such as FNAC supplemented by good clinical history taking still are a saviour for reaching a diagnosis. 15 Early recognition with prompt treatment is mandatory to prevent sequelae of candidiasis and its haematogenous or contiguous spread. 6…”
Section: Discussionmentioning
confidence: 99%